2023
DOI: 10.3390/clockssleep5010008
|View full text |Cite
|
Sign up to set email alerts
|

Does Motor Memory Reactivation through Practice and Post-Learning Sleep Modulate Consolidation?

Abstract: Retrieving previously stored information makes memory traces labile again and can trigger restabilization in a strengthened or weakened form depending on the reactivation condition. Available evidence for long-term performance changes upon reactivation of motor memories and the effect of post-learning sleep on their consolidation remains scarce, and so does the data on the ways in which subsequent reactivation of motor memories interacts with sleep-related consolidation. Eighty young volunteers learned (Day 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The evolution of performance with time and practice is consistent with previous findings. 38 , 39 Concerning the absence of a sleep effect on delayed performance, other reports also found that post-learning sleep did not systematically result in increased performance at delayed retest. 40 , 41 , 42 Especially when focusing on the SRTT literature, sleep-related effects were not consistently observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The evolution of performance with time and practice is consistent with previous findings. 38 , 39 Concerning the absence of a sleep effect on delayed performance, other reports also found that post-learning sleep did not systematically result in increased performance at delayed retest. 40 , 41 , 42 Especially when focusing on the SRTT literature, sleep-related effects were not consistently observed.…”
Section: Discussionmentioning
confidence: 95%
“… 60 Also, the morning retest on Day 2 might have helped the SD group to catch up by reactivating the memory trace; however, this has been found to be without consequences in a similar protocol, at least at the behavioral level. 39 We also obtained diffusion MRI scans at the outset of the RS/SD night experimental night in the morning of Day 2 (not reported here), but these were not suitable for investigating this issue due to contamination by the lack of sleep 61 , 62 , 63 and circadian confounds that have been found to influence structural measures taken 12 h apart. 64 , 65 …”
Section: Discussionmentioning
confidence: 99%
“…60 Also, the morning retest on Day 2 might have helped the SD group to catch up by reactivating the memory trace; however, this has been found to be without consequences in a similar protocol, at least at the behavioral level. 39 We also obtained diffusion MRI scans at the outset of the RS/SD night experimental night in the morning of Day 2 (not reported here), but these were not suitable for investigating this issue due to contamination by the lack of sleep [61][62][63] and circadian confounds that have been found to influence structural measures taken 12 h apart. 64,65 Lastly, we hypothesized that microstructural parameters would change again when re-exposed to the initial motor task and that these changes could be modulated by the sleep opportunity on the post-learning night, as shown in a prior study investigating topographical learning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, post-learning sleep was proposed to contribute to the consolidation of motor memories. Amongst others, supporting evidence comes from studies showing enhanced motor performance after a post-learning nap episode 5-10 and robust motor performance benefits after overnight sleep 11 (but see, e.g., [12][13][14][15] for discrepant results). Noticeably, studies on the dynamics of post-learning nap long-term consolidation were found inconsistent, with post-nap motor performance gains either found to vanish 16 or persist 5 after a full night of sleep.…”
mentioning
confidence: 99%